The Influence of Compensation, Work Environment, and Job Stress on Employee Job Satisfaction at PT Indomarco Prismatama - Muhammad Hibbanduta; Renny Husniatir; Syarif Ali; Suryani Maryam (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research is a quantitative research that aims to determine the influence of work environment and work stress on job satisfaction. This study used 54 employees of PT Indomarco Prismatama and employees of Indomaret outlets in Pancoran, South Jakarta as samples. The analysis technique used in this study is descriptive analysis technique and inferential analysis using the SmartPLS 3.2.9 test tool. Testing the hypothesis in this study using the T test with a significance level of 5% (0.05). The research results show (1) compensation have a positive and significant influence on job satisfaction; (2) the work environment has a positive and significant influence on job satisfaction; (3) work stress has a positive and significant effect on job satisfaction; and (4) compensation, work environment and work stress have a significant effect simultaneously on employee job satisfaction